Transcriptional response of Cu-deficient barley (Hordeum vulgare L.) to foliar-applied nano-Cu: Molecular crosstalk between Cu loading into plants and changes in Cu homeostasis genes - Kusiak, Magdalena; Sozoniuk, Magdalena; Larue, Camille; Grillo, Renato [UNESP]; Kowalczyk, Krzysztof; Oleszczuk, Patryk; Jośko, Izabela (Elsevier, 2023)
For safe and effective nutrient management, the cutting-edge approaches to plant fertilization are continuously developed. The aim of the study was to analyze the transcriptional response of barley suffering from Cu deficiency to foliar application of nanoparticulate Cu (nano-Cu) and its ionic form (CuSO4) at 100 and 1000 mg L−1 for the examination of their supplementing effect. The initial interactions of Cu-compounds with barley leaves were analyzed with spectroscopic (ICP-OES) and microscopic (SEM-EDS) methods. To determine Cu cellular status, the impact of Cu-compounds on the expression of genes involved in regulating Cu homeostasis (PAA1, PAA2, RAN1, COPT5), aquaporins (NIP2.1, PIP1.1, TIP1.1, TIP1.2) and antioxidant defense response (SOD Cu[sbnd]Zn, SOD Fe, SOD Mn, CAT) after 1 and 7 days of exposure was analyzed. Although Cu accumulation in plant leaves was detected overtime, the Cu content in leaves exposed to nano-Cu for 7 days was 44.5% lower than in CuSO4 at 100 mg L−1. However, nano-Cu aggregates remaining on the leaf surface indicated a potential difference between measured Cu content and the real Cu pool present in the plant. Our study revealed significant changes in the pattern of gene expression overtime depending on Cu-compound type and dose. Despite the initial puzzling patterns of gene expression, after 7 days all Cu transporters showed significant down-regulation under Cu-compounds exposure to prevent Cu excess in plant cells. Conversely, aquaporin gene expression was induced after 7 days, especially by nano-Cu and CuSO4 at 100 mg L−1 due to the stimulatory effect of low Cu doses. Our study revealed that the gradual release of Cu ions from nano-Cu at a lower rate provided a milder molecular response than CuSO4. It might indicate that nano-Cu maintained better metal balance in plants than the conventional compounds, thus may be considered as a long-term supplier of Cu.
Keywords: Antioxidants; Aquaporins; Engineered nanoparticles; Gene expression; Metal transporters